From Crisis to IMF-Supported Program : Does democracy impede the speed required by financial markets? - Mody, Ashoka; Saravia, Diego (Washington, D.C. : International Monetary Fund, 2008)
Has the spread of democracy and political participation impeded the need for speed required by financial markets and the elevated threat of contagion across borders? We examine the time span between the onset of a financial crisis and the agreement on an IMF-supported adjustment program. This span appears to have decreased over time. More precisely, we find that the time from a crisis to the approval of a program has been smaller the more serious the crisis. Importantly, this responsiveness to a widening range of financial vulnerabilities has increased with growing financial integration. Democracies, particularly those with checks and balances, have been sensitive to time pressures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet